Pengaruh Aplikasi Muzaki Corner Terhadap Minat Masyarakat Berzakat - Muhammad Kambali; Fatur Rahman (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2021)
This research aims to show the effect of using the muzaki corner application on muzaki interest in tithing. The research method uses a quantitative approach. The population in this study were all muzaki of the Gresik National Amil Zakat Agency, who used the muzaki corner application. The sample in this study was 80 respondents. Data were collected through questionnaires with an accidental sampling technique. Data were analyzed using simple linear regression, hypothesis testing, and coefficient of determination. The results showed that using the muzaki corner application affected people's interest in tithing, with an effect of 92.3%. In comparison, 7.7% was influenced by other factors that were not included in this research model. This research can strengthen the growth and development of public interest in tithing at the National Amil Zakat Agency.